Fresh Money for Health? The (False?) Promise of "Innovative Financing" for Health in Malawi. Issue 4 (2nd October 2018) - Chansa, Collins; Mwase, Takondwa; Matsebula, Thulani Clement; Kandoole, Priscilla; Revill, Paul; Makumba, John Bosco; Lindelow, Magnus
Abstract: Since 2013, the government of Malawi has been pursuing a number of health reforms, which include plans to increase domestic financing for health through "innovative financing." As part of these reforms, Malawi has sought to raise additional tax revenue through existing and new sources with a view to earmarking the revenue generated to the health sector. In this article, a systematic approach to assessing feasibility and quantifying the amount of revenue that could be generated from potential sources is devised and applied. Specifically, the study applies the Delphi forecasting method to generate a qualitative assessment of the potential for raising additional tax revenues from existing and new sources, and the gross domestic product (GDP)-based effective tax rate forecasting method to quantify the amount of tax revenue that would be generated. The results show that an annual average of 0.30 USD, 0.46 USD, and 0.63 USD per capita could be generated from taxes on fuel and motor vehicle insurance over the period 2016/2017–2021/2022 under the low, medium, and high scenarios, respectively. However, the proposed tax reform has not been officially adopted despite wide consultations and generation of empirical evidence on the revenue potential. The study concludes is that revenue generation potential of innovative financing for health mechanisms in Malawi is limited, and calls for efforts to expand fiscal space for health to focus on efficiency-enhancing measures, including strengthening of governance and public financial management.